A Review Using Artificial Intelligence-Generating Images: Exploring Material Ideas from MidJourney to Improve Vernacular Designs - Stephen Tanugraha (Journal of Artificial Intelligence in Architecture, 2023)
Artificial Intelligence (AI) was created to be an assistant to humankind. The architectural design process is one of them.   Artificial Intelligence is starting to enter the realm of architecture and design. Lately, teams have developed many AI algorithms to generate random images based on the database they had just by texting a command for them. MidJourney is a discord-based Artificial Intelligence for generating images with the text-to-images method, and its database is infinite; it can suggest incredible things. Architects can use MidJourney as a design ideas generator with specific commands.  MidJourney, one of the AI pioneers in the design world, still has many shortcomings and limitations. Incorrect details and forms are one of its limitations. This exploration using AI should be deepened as part of MidJourney development. This study aims to discover how far researchers have done the command prompt in exploring MidJourney in architecture. This research can be the basis for further research in developing the text-to-image Artificial Intelligence Generator results. This paper uses a systematic literature review method on journals, books, and websites linked with Artificial Intelligence, architecture, and texture selection for building. The systematic literature review involves collecting questions, identifying keywords, screening articles, analyzing, discussing, and concluding.                    The results explain the role of Artificial Intelligence in architectural design. MidJourney can choose the proper material for its innovations by generating concept ideas. However, MidJourney has yet to be able to implement the logic of structures and buildings in its design even though it has used architecture-related prompts, perhaps because it was not specifically designed to produce architectural drawings but graphic design only. The challenge is based on the user defining the limitation and the main ideas for generating Artificial Intelligence.